Application of The Rapid Application Development Method to Develop a Decision Support System for Employee Performance Assessment in a State-Owned Electricity Company - Fermica Iskandar, Merissa; Dharmawan, Donny; Kusnady, Diding; Sintesa, Nika; Arijanti, Susi (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to create a decision support system for employee performance evaluation that will help managers choose qualified applicants for advancement. In this study, observation, interviews, and literature review were employed as data collection techniques. RAD is the system development methodology that the author used in this study. Black box testing is used for testing. The following conclusions were drawn from the research's findings: first, it created a helpful decision support system that helped managers judge employee promotions by giving them more objectivity. This system helps managers make more accurate and equitable promotion decisions by offering rewards for evaluating employee performance. Second, this research contributes to the field by developing a decision support system visually representing employee performance metrics using graphs. Using the MFEP and MPE methods in the system provides a clear and easy-to-understand picture of employee performance. With graphs, managers can quickly and efficiently evaluate employee performance data, facilitating decision-making.